Malay version of the Michigan hand outcomes questionnaire: cross-cultural adaptation and reliability testing in Kuantan, Pahang - Lye, Jun Xiong; Kow, Ren Yi; Ismail, Raffael; Khalid, Kamarul Ariffin (Kulliyyah of Allied Health Sciences, International Islamic University Malaysia, 2019)
The Michigan Hand Outcomes Questionnaire (MHQ), a self-reported questionnaire for patients with hand disorders, has been widely used globally. It has been cross-culturally adapted into different languages across all continents. Aims of this study were to translate the MHQ into Malay language and to evaluate its reliability in a Malay-speaking population. The MHQ was cross-culturally adapted into a Malay version based on Beaton et al. guidelines. A pre-testing involving thirty patients with hand disorders was performed to assess whether it was comprehensible to the target population. One hundred patients with hand disorders were recruited in this study to answer the MHQ twice with an interval of two weeks. Statistical analysis was performed to assess the reproducibility and internal consistency via the test-retest method (Intraclass correlation coefficient analysis) and Cronbach’s alpha calculation, respectively. In the pre-testing, twenty-six patients (86.7%) understood all the questions in the Malay version of MHQ. The test-retest analysis showed good reliability across the duration of two weeks with the intraclass correlation coefficient of all subscales ranged from 0.925 to 0.984. Cronbach’s alpha values of the Malay version MHQ ranged from 0.82 to 0.97, indicating a good internal consistency. The Malay version of MHQ has been successfully translated and culturally-adapted with good reliability and internal consistency.